Estimating willingness to pay for a payment forest ecosystem services scheme, Gunung Tebu forest reserve in Malaysia as a case study - Y., Mohd Rusli; M, Mohd Parid; A, Mukrimah; M., Nitanan Koshy; S, Faizah (International Organization of Scientific Research, 2023)
The conceptualization of payments for ecosystem services (PES) is essential for sustainable financing mechanisms for the provision of environmental goods and services. Through the goal of PES programs, sustainable forest management can be achieved by securing forest-derived benefits to support conservation and sustainable livelihoods. The purpose of this study was to determine public Willingness to Pay (WTP) for a payment for forest ecosystems services scheme in Gunung Tebu Forest Reserve, Malaysia. The Contingent Valuation Method (CVM) that involved double bounded dichotomous choice was used in this study. A face-to-face interview which involved 375 respondents in Terengganu was collected between May to September 2022. The data were analysed using the conditional logit and mixed logit models. The findings revealed that the respondents are willing to pay significantly per year to improve the attributes of ecosystem services in Gunung Tebu Forest Reserve (GTFR), Terengganu, Malaysia. This finding shows that PES is a promising program to support forest conservation efforts. This study also enlightens the direction for policymakers to develop the future PES program to support forest conservation.